Users Perception of Social Media on Political Satire in Political Memes in Indonesia - Ansar Suherman (International Journal of Advanced Science and Technology, 2020)
Political satire emerged in the political years in Indonesia, especially before the presidential and vice-presidential elections of the Republic of Indonesia in 2019. One form of political satire is contained in political memes on social media. The use of social media to spread political memes can reach a wider audience. The phenomenon of the emergence of political memes by many Indonesians is motivated by social pressure and political turmoil of political elites at the national or local level, so that many creative ideas emerge to eliminate boredom. Not just to get rid of boredom, but to provide entertainment. This meme is a medium that conveys information through humor, and figuratively has long been a tool of resistance. This study looks at political memes that exist in several social media, namely Facebook and Instagram. The purpose of this study is to analyze the perception of social media users about political innuendo contained in social media accounts using a qualitative approach. The findings in this study are that political memes in Indonesia have become one of the media that provides ideas and criticisms of social and political life phenomena that are of interest to the political elite and to direct the government. In addition, several factors were found that caused differences in the perception of social media users about the content of political memes. The conclusion is the background of the level of education and the background of cultural values ​​adopted by the informant are the factors that distinguish these perceptions.